A Disability Studies in Education Analysis of the edTPA Through Teacher Candidate Perspectives. (November 2017) - Bacon, Jessica; Blachman, Sheila
This analysis of the Special Education edTPA is written by two professors who co-taught a student teaching seminar at one institution and supported the first groups of teacher candidates required to submit the edTPA for certification in New York State. Data were gathered over three semesters and included open-ended student surveys, student journals, and public documents. Findings describe (a) how the edTPA requirements impacted teacher candidate learning, (b) the emphasis on one focus learner in the exam, (c) the discourse and language demands in the edTPA, and (d) how the edTPA and videotaping impacted fieldwork. We describe these findings and discuss their implications for inclusive and Special Education as understood through a disability studies in education perspective.